2011
DOI: 10.1074/jbc.m110.168583
|View full text |Cite
|
Sign up to set email alerts
|

Strong Cross-bridges Potentiate the Ca2+ Affinity Changes Produced by Hypertrophic Cardiomyopathy Cardiac Troponin C Mutants in Myofilaments

Abstract: This spectroscopic study examined the steady-state and kinetic parameters governing the cross-bridge effect on the increased Ca 2؉ affinity of hypertrophic cardiomyopathy-cardiac troponin C (HCM-cTnC) mutants. Previously, we found that incorporation of the A8V and D145E HCM-cTnC mutants, but not E134D into thin filaments (TFs), increased the apparent Ca 2؉ affinity relative to TFs containing the WT protein. Here, we show that the addition of myosin subfragment 1 (S1) to TFs reconstituted with these mutants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…Human TnC WT , TnC A8V , and TnI were recombinantly expressed and purified according to established protocols (25,28). …”
Section: Methodsmentioning
confidence: 99%
“…Human TnC WT , TnC A8V , and TnI were recombinantly expressed and purified according to established protocols (25,28). …”
Section: Methodsmentioning
confidence: 99%
“…Pinto et al . reported that cTnC A8V and cTnC D145E significantly slowed Ca 2+ dissociation kinetics ( k off ) in solution, suggesting both mutations may alter muscle relaxation properties [178]. Considering that most of the findings of these HCM mutations were focused on the Ca 2+ sensitivity of ATPase activity and/or force development, it is of importance to also investigate how they influence the muscle relaxation.…”
Section: Ctn Mutations Associated With Familial Hypertrophic Cardiomymentioning
confidence: 99%
“…This gives an overall stoichiometry between the thin filament and S1 as 1:1.58, respectively. We have previously determined that this is the ideal concentration/ratio of S1 that caused the half-maximal change in fluorescence from thin filaments (24). The change in the fluorescence spectra was recorded during the titration of microliter amounts of CaCl 2 .…”
Section: Functional and Structural Studiesmentioning
confidence: 99%